What was literary impressionism? - Fried, Michael (The Belknap Press of Harvard University Press, 2018)
The most famous statement associated with the idea of literary impressionism is Joseph Conrad's from the Preface to The Nigger of the "Narcissus" (1897): "My task, which I am trying to achieve is, by the power of the written word, to make you hear, to make to feel - it is, before all, to make you see! That - and no more: and it is everything!" What exactly Conrad meant by "make you see" has, of course always been a question, but all commentators have been agreed that it chiefly concerned with making the reader visualize the scenes narrated by the writer. This book argues that what is distinctive about English-language literary impressionism - a movement or tendency the author locates chronologically between 1890 and 1914 - is not only the desire to make the reader see but also, crucially, what it is the reader is to be made to see. The authors treated in this study include Stephen Crane, Joseph Conrad (four of whose novels are analyzed in detail), Frank Norris, W.H. Hudson, Ford Madox Ford, H.G. Wells, Jack London, Rudyard Kipling, Erskine Childers, R.B. Cunninghame Graham, Edgar Rice Burroughs, and Robert Louis Stevenson.--